Effective message synchronization methods for multiplayer online games with maps. - Paik, Doowon; Yun, Chung-Ha; Hwang, Jooyeon (Computers in Human Behavior, 2008)
A solution for the message synchronization problem of the client-server based game system is to wait for a certain period of time (waiting period) until the server processes the messages from clients. However, identifying a suitable waiting period proves challenging. In this paper, we develop two methods to determine the waiting period using the probability of interaction among participants and ranking of the delay among participants. Our methods take advantage of the property of games with geographical mapping, where each participant usually interacts with other participants only in the immediate surroundings. Simulation is performed for the evaluation of the methods and the shows that the proposed methods produce better results with lower average unfair ratio while keeping the same responsiveness compared to the method with prefixed waiting period. Copyright (c) 2008 Elsevier Ltd.